CHARACTERISTICS OF FORMS AND MEANINGS OF VERBAL EXPRESSIONS ABOUT GOD’S EXISTENCE IN SABUNESE - Hendrina Pada; Frans Bustan; Tans Feliks; Labu Juli; Alex Djawa (Postgraduate School, Universitas Nusa Cendana, 2019)
Sabu Raijua society is a society that is polytheism. They believe many Deo 'Gods and Goddesses' in their lives. They believe that Deo 'God and Goddess' has a different role. Every god and goddess has the character, form and meaning contained in each name. In general, the names of Gods and Goddess in accordance with their role, there is no name that refers to his name. Gods and Goddesses in general have good character, patience, loyalty, helpers, protectors, guardians, and maintainers.